FREQUENCY OF CHRONIC COMPLICATION IN TYPE 2 DIABETES AT ATERTIARY CARE HOSPITAL IN THE PROVINCE OF PUNJAB - Muhammad Azfar Tanveer; Sammiullah Douna; Aymon Shafi; Shahnawaz Hasan Gardezi; Farooq Mohyud Din Chaudhary; Ghulam Mohyud Din Chaudhry (Baqai Journal of Health Sciences)
Objective: To find out the frequency of chronic complications among type 2 diabetic subjects in a Tertiary Care Hospital in the province of Punjab.